2023
DOI: 10.3390/life13020508
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID-19 Syndrome Severity According to Sex, Time from the Onset of the Disease, and Exercise Capacity—The Results of a Cross-Sectional Study

Abstract: Symptoms of long COVID-19 syndrome (long COVID-19) are reported by 80% of convalescents up to several months after contracting the coronavirus-19 disease (COVID-19). The study aimed to assess the frequency and correlations of long COVID symptoms with sex, disease severity, time since the onset of the disease, and exercise capacity in a population of Polish convalescents hospitalized as a part of a rehabilitation program after COVID-19. The retrospective analysis was carried out based on medical records concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…As in other studies, our patient population showed a reduced VO2 max as well as a reduced walking distance in the 6MWT [27][28][29]. The performance in percentage was more limited in the maximal ranges than in the submaximal range, although the FAS correlated significantly only with the 6MWT performance, a finding also observed in other studies [6], and tended to correlate with VO2 max . Possible causes of impaired cardiopulmonary fitness can be, in addition to reduced fitness even before the onset of the disease, a further reduction due to inactivity and a sedentary lifestyle because of COVID-19 related symptoms [29] or government-ordered measures of quarantine [30,31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As in other studies, our patient population showed a reduced VO2 max as well as a reduced walking distance in the 6MWT [27][28][29]. The performance in percentage was more limited in the maximal ranges than in the submaximal range, although the FAS correlated significantly only with the 6MWT performance, a finding also observed in other studies [6], and tended to correlate with VO2 max . Possible causes of impaired cardiopulmonary fitness can be, in addition to reduced fitness even before the onset of the disease, a further reduction due to inactivity and a sedentary lifestyle because of COVID-19 related symptoms [29] or government-ordered measures of quarantine [30,31].…”
Section: Discussionsupporting
confidence: 88%
“…Approximately 80% of hospitalized and non-hospitalized patients have symptoms lasting longer than 12 months [3]. Important risk factors associated with PCS appears to be pre-existing illnesses (especially cardiorespiratory, autoimmune and oncological previous diseases, and neuropsychiatric disorders), female gender, respiratory symptoms at onset, length of hospital stay and severity of illness, although milder courses also can trigger PCS [1,[4][5][6]. The most common symptoms that contribute mainly to decreased health recovery and reduced resilience include fatigue, reduced exercise tolerance and muscular strength, neurocognitive problems, muscle pain and dyspnea [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those of previous studies. [16][17][18][19] Moreover, our analyses showed that admission was associated with increased functional limitations and/or mortality after discharge. Previous studies described functional impairments following ICU admission owing to COVID-19 and other critical illnesses.…”
Section: Discussionmentioning
confidence: 61%
“…We found that depression is widespread in patients have survived COVID-19, especially in women, and often co-exists with fatigue, dyspnea, and cognitive dysfunction, affecting patients’ quality of life [62, 63]. Therefore, psychological support and psychiatric intervention should be considered during the process of cardiac rehabilitation (Fig.…”
Section: Long-covid and Its Cardiovascular Sequelaementioning
confidence: 99%